Vesicular traffic-mediated cell-to-cell signaling at the immune synapse in Ankylosing Spondylitis - Tavasolian, Fataneh; Pastrello, Chiara; Ahmed, Zuhaib; Jurisica, Igor; Inman, Robert D. (Frontiers in Immunology, 2023)
The chronic inflammatory disease ankylosing spondylitis (AS) is marked by back discomfort, spinal ankylosis, and extra-articular symptoms. Inflammation is responsible for both pain and spinal ankylosis, but the processes that sustain it remain unknown. Despite the years of research, little progress has been made in identifying the signaling events that lead to the development of this disease. T cells, an immune cell type that initiates and regulates the body's response to infection, have been demonstrated to have a significant role in the development of AS. T lymphocytes are regarded as a crucial part of adaptive immunity for the control of the immune system. A highly coordinated interaction between antigen-presenting cells (APCs) and T cells that control T cell activation constitutes an immunological synapse (IS). This first phase results in the polarized trafficking of receptors and signaling mediators associated with folding endosomes to the cellular interface, which contributes to IS assembly and signal termination and facilitates the passage of information from T cells to APCs. Discrimination of self and nonself antigen is somatically learned in adaptive immunity, and in an autoimmune condition such as AS, there is a disturbance of self/ nonself antigen discrimination; available findings clearly imply that the IS plays a preeminent role in the adaptive immune response. In this paper, we provide insights into the genesis of AS by evaluating recent developments in the function of vesicular trafficking in IS formation and the targeted release of exosomes enriched microRNAs (miRNA) at the synaptic region in T cells.